Keteng-Keteng Development of Three Bamboo Sections - Adina S. Sembiring; Uyuni Widiastuti; Brepin Tarigan; Lamhot B Sihombing; Hendy Obed Sembiring; Ewin Johan Sembiring (Britain International for Academic Research (BIAR) Publisher, 2020)
Traditional music is music that has the characteristics of a tribe or layer of society. One of the traditional Karo music is Keteng-keteng which is played by beating with two sticks. The keteng-keteng is made of buluh belin (large bamboo), the tip and base have bamboo skin. So far, keteng-keteng is made from one segment of bamboo, therefore the aim of this research is to develop keteng-keteng from one bamboo segment to three bamboo sections (telu ngawan) using electricity. These kettles will later use an electronic equalizer, so that the sound of the kettles produced is really an equalizer standard, which can be adjusted according to the color of the sound on the middle bass and treble. The keteng-keteng being developed is a combination of the three-segmented ketengs, the daluna-ketengs and the multi-purpose kettles, which are combined into three sections of bamboo. This is the first time this merger has been done by researchers. From this combination, two gung characters are found. which is different because Beruna uses vibrating aids while Daluna does not use vibrating aids.